2009
DOI: 10.1093/eurheartj/ehp458
|View full text |Cite
|
Sign up to set email alerts
|

The impact of early standard therapy on dyspnoea in patients with acute heart failure: the URGENT-dyspnoea study

Abstract: When sitting upright, dyspnoea in the sitting position improves rapidly and substantially in patients with AHF after administration of conventional therapy, mainly intra-venous diuretics. However, many patients remain orthopnoeic. Improving the methodology of clinical trials in AHF by standardizing the conditions under which dyspnoea is assessed could enhance their ability to identify effective treatments. Relief of orthopnoea is clinically valuable and may represent a useful goal for clinical trials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
107
0
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 167 publications
(114 citation statements)
references
References 20 publications
4
107
0
3
Order By: Relevance
“…Other studies that focused on dyspnoea relief suggested that earlier initiation of therapy provides greater symptom relief 27. However, in one study, only two‐thirds of the enrolled patients with a suspected diagnosis of AHF within 1 h of presentation were confirmed to have AHF at 6 h after presentation, suggesting that too rapid enrolment might result in patients without AHF being included in the trial 28. In both Pre‐RELAX‐AHF21 and RELAX‐AHF19 patients were randomized within 16 h of presentation at a median of 8–9 h; this time frame is the goal for RELAX‐AHF‐2 as well.…”
Section: Discussionmentioning
confidence: 98%
“…Other studies that focused on dyspnoea relief suggested that earlier initiation of therapy provides greater symptom relief 27. However, in one study, only two‐thirds of the enrolled patients with a suspected diagnosis of AHF within 1 h of presentation were confirmed to have AHF at 6 h after presentation, suggesting that too rapid enrolment might result in patients without AHF being included in the trial 28. In both Pre‐RELAX‐AHF21 and RELAX‐AHF19 patients were randomized within 16 h of presentation at a median of 8–9 h; this time frame is the goal for RELAX‐AHF‐2 as well.…”
Section: Discussionmentioning
confidence: 98%
“…9,10,12,13 These studies demonstrate that contemporary ADHF therapy is suboptimal not only with respect to outcomes, 21 but also with respect to symptom relief. 22 Therefore, it is important to understand the reasons for the failure to improve dyspnea.…”
Section: Discussionmentioning
confidence: 99%
“…There has been enormous growth in knowledge about the neurophysiology of dyspnea. In addition, there has been growing interest in the potential use of dyspnea as a patient-reported outcome in clinical trials of pharmacologic and nonpharmacologic interventions in patients with cardiopulmonary disease (17,18).…”
Section: Introductionmentioning
confidence: 99%